Immigration and acculturation : mourning, adaptation, and the next generation - Akhtar, Salman, 1946 July 31- (Jason Aronson, 2011)
Moving from one country to another causes a radical alteration of one's cultural and geophysical surround. Separation from friends and family, loss of valued possessions, and encountering new ways of living result in mental pain and disorienting anxieties. In Immigration and Acculturation, Salman Akhtar examines the traumatic impact of immigration and the acculturation process and the psychological defenses that are mobilized in the immigrant, including nostalgia and fantasies of return. Akhtar explores each aspect of an immigrant's life, shedding light on the complexities of work, friendship.